Pain management for the Nuss procedure: comparison between erector spinae plane block, thoracic epidural, and control - Lisgelia Santana; John Driggers; Norman F Carvalho (BMJ Publishing Group, 2022)
Objective Pectus excavatum is a congenital deformity characterized by a caved-in chest wall. Repair requires surgery. The less invasive Nuss procedure is very successful, but postoperative pain management is challenging and evolving. New pain management techniques to reduce opioid reliance include the erector spinae plane (ESP) block. We retrospectively examined opioid consumption after Nuss procedure comparing three pain management techniques: ESP block, thoracic epidural (TE), and patient-controlled analgesia (PCA).Methods This retrospective cohort study compared pain management outcomes of three patient groups. Seventy-eight subjects aged 10-18 years underwent Nuss procedure at our institution between January 2014 and January 2020. The primary outcome measure was opioid consumption measured in morphine milligram equivalents. Secondary measures included pain ratings and length of stay (LOS). Pain was quantified using the Numeric Pain Rating Scale. Analysis of variance was performed on all outcome measures.Results Average cumulative opioid use was significantly lower in the ESP block (67 mg) than the TE (117 mg) (p=0.0002) or the PCA group (172 mg) (p=0.0002). The ESP block and PCA groups both had a significantly shorter average LOS (3.3 and 3.7 days, respectively) than the TE group (4.7 days). ESP block performed best for reducing opioid consumption and LOS. Reduced opioid consumption is key for limiting side effects. This study supports use of ESP block as a superior choice when choosing among the three postoperative pain management options that were evaluated.Conclusion ESP resulted in reduced opioid consumption postoperatively and shorter LOS than TE or PCA for patients undergoing the Nuss procedure for surgical repair of pectus excavatum.